Actualization of the public participation report in the regional mining management to encourage public accessibility to mining business information - Bagus Putra Handika Pradana; Nabila; Putri Larasati Ayuningrum (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Local regulations governing mineral and rock mining activities often fail to clearly establish reporting mechanisms regarding public participation. This lack of transparency limits public access to mining management data, thereby exacerbating widespread environmental damage. To mitigate this ecological damage, incorporating structured public participation reports into the local regulatory framework is essential to legally ensure community involvement. Methods: Researched using normative legal research methods with descriptive-qualitative analysis techniques. The approaches used are the statutory regulatory approach and the conceptual approach. Findings: The results of this study indicate that; Special Region of Yogyakarta Regional Regulation No. 1 of 2018 concerning mining business management must clearly regulate the existence of a public participation report; second, efforts to actualize the public participation report in Regional Regulation No. 1 of the Province of Special Region of Yogyakarta to encourage public accessibility to information, data, and documents on public participation reports in mining management business activities in Special Region of Yogyakarta. Conclusion: This research is oriented towards alleviating the problems faced by the community. Thus, formulation is created that makes the community objectivity by creating an effective moral compass in overseeing mining business activities in Special Region of Yogyakarta Province. Novelty/Originality of this article: This study introduces the conceptual framework of the “Public Participation Report” as a mandatory legal document in mining governance at the local level, shifting the paradigm of public engagement from a mere procedural formality to a legally binding instrument in terms of environmental accountability and information equity.